Synthetic and biosynthetic routes to nitrogen-nitrogen bonds - He, Hai-Yan; Niikura, Haruka; Du, Yi-Ling; Ryan, Katherine S (Chemical Society reviews, 2022)
The nitrogen-nitrogen bond is a core feature of diverse functional groups like hydrazines, nitrosamines, diazos, and pyrazoles. Such functional groups are found in >300 known natural products. Such N-N bond-containing functional groups are also found in significant percentage of clinical drugs. Therefore, there is wide interest in synthetic and enzymatic methods to form nitrogen-nitrogen bonds. In this review, we summarize synthetic and biosynthetic approaches to diverse nitrogen-nitrogen-bond-containing functional groups, with a focus on biosynthetic pathways and enzymes.